Reaction of Beta-Carotene with Metal Ions - Products Isolation and Characterisation - Yii, Mei Woo (1998)
Reaction of β-carotene with ferric nitrate nonahydrate and anhydrous stannous chloride has been carried out. A π-complex of iron-β-carotene,Fe(N03)3.C40H56.2CH2Ch, been synthesized and characterized. No product was isolated from the reaction between stannous chloride and β-carotene. The structure of the iron-β-carotene complex was proposed on the basis of IR andUV -Vis spectra and elemental analyses.